Analisis Pembiasaan Perilaku Berliterasi dalam Upaya Peningkatan Karakter oleh Siswa Kelas VI SD - Sandy Mardian Damanik; Desi Mayasari; Ade Surnizal; Andriani Hasibuan; Supinah Supinah; Erwita Erwita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Beginning reading and writing are stages of the learning process for elementary school students. Various studies have shown that the habit of reading quality literature contributes to a person's level of intelligence. Reading helps someone to see problems from various perspectives and consider them as challenges that must be solved. It's the same with literacy. Has the meaning and implications of basic reading and writing skills to the acquisition and manipulation of knowledge through written texts, from the metalinguistic analysis of grammatical units to the structure of spoken and written texts. From the several survey institutions, Indonesia ranks bottom and this shows that literacy skills in Indonesia are still low. This research aims to determine the literacy skills of students at SMP St. Ignatius and know the right strategy to improve students' literacy skills. Exclusive data collection was carried out in class VI with a total of 22 students. This research starts from October to December 2022. The results of this mini research are that the class mini library is efficient for students' reading habits. Then, it can be seen that students basically have a desire to read even though there are those who read only at a glance and see the title first. This can be overcome if the teacher regularly pays attention to students' reading activities until finally they get used to reading activities. Thus it can be concluded that SD Negeri 165730 students are still at the stage of reading habit. Keywords: books, literacy, students, mini library, school